Tests on ferritic stainless steel simply supported and continuous SHS and RHS beams. Issue 4 (November 2016) - Arrayago, Itsaso; Real, Esther; Mirambell, Enrique
Abstract: Development of efficient design guidance for stainless steel structures (considering non‐linear behaviour, strain hardening and allowing for moment redistribution in indeterminate structures) is crucial for the widespread use of this corrosion‐resistant material. This paper presents an experimental programme involving ferritic stainless steel simply supported and continuous beams (RHS and SHS) and the assessment of existing cross‐sectional classifications and different plastic design methods available in the literature for indeterminate stainless steel structures, not currently allowed in stainless steel standards. The analysis indicated that some cross‐sectional classification limits seem to be too optimistic for ferritic stainless steels and further research is needed in order to extend plastic design to these grades.